Pondok Pesantren Internasional Di Surakarta Dengan Pendekatan Arsitektur Islam - Wartono, Kostrad Hari; , Dr. Ir.Widyastuti Nurjayanti,MT; , Ir.Nurhasan,MT (2015)
International Boarding School in Surakarta planned is a boarding school as a place of Islamic education activities that have values ​​of Islam and became an icon for the development of Islam. events that arise with the development of the religion of Islam itself and is linked to a boarding school, like the DI / TII, the case of the first Bali bombing, the second Bali bombing, and other events led to the development of negative opinions public on the education system boarding school, which can not be separated from detailing activities of terrorism. Now many developing boarding schools that also incorporate general education science education in the curriculum, the boarding school is called as a modern boarding school. Modern boarding school has been a bit much to change the paradigm and society's negative opinion on the boarding school, because many people who want education that can meet the religious sciences but also did not lag behind in science education generally. Based on the description above, we plan and design the International Islamic boarding school in Surakarta. Design planned by Islamic architecture approach consisting of a) .The room Class-room for students son b) Spaces class for women students c) .Masjid d) .The room business e) .The room Eating Together Sons and Daughters, f) .Asrama Pupils Son and Daughter g) .Home Ustadz and Ustadzah h) .Fasilitas Parking Keywords: boarding school, Internasional.Surakarta